PERAN GURU DALAM MENGATASI MASALAH KEDISIPLINAN BELAJAR SISWA SEKOLAH DASAR - Waridah Waridah; Saprianto Saprianto; Eko Fery HS (Bestari: Jurnal Pendidikan dan Kebudayaan, 2023)
: This study aims to find out how the role of teachers in overcoming student learning discipline problems in elementary schools. This type of research is qualitative with a qualitative descriptive approach. The subjects of the study were 1 class teacher and 14 grade 5 students of SD Negeri 09 Tanjung Lay, with the object of research on the role of teachers in overcoming student learning discipline problems. The instruments used are interview guidelines, observation guidelines and documentation. The results of the study found 7 forms of roles used by the teacher to overcome the problem of student learning discipline, namely the role of the teacher as a teacher, as a guide, as a motivator, as a demonstrator, as a manager and as a counselor. Teachers use various ways to overcome student learning discipline problems such as providing motivation and appreciation, being an example and role model, guiding and embracing students and giving punishment with positive goals, time and action discipline, making approaches according to student characteristics and needs, evaluating results student learning as well as implementing student attendance zones to discipline student attendance time.